2017
DOI: 10.1186/s13098-017-0298-x
|View full text |Cite
|
Sign up to set email alerts
|

Favourable metabolic profile sustains mitophagy and prevents metabolic abnormalities in metabolically healthy obese individuals

Abstract: BackgroundObesity-mediated oxidative stress results in mitochondrial dysfunction, which has been implicated in the pathogenesis of metabolic syndrome and T2DM. Recently, mitophagy, a cell-reparative process has emerged as a key facet in maintaining the mitochondrial health, which may contribute to contain the metabolic abnormalities in obese individuals. However, the status of mitophagy in metabolically healthy obese (MHO) and metabolically abnormal diabetic obese (MADO) subjects remains to be elucidated. Henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Mitochondria are the key intracellular targets for Cd stress (Bhansali et al, 2017), and Cd exposure can damage the integrity of the mitochondria in aquatic organisms, both structurally and functionally (Adiele et al, 2011) Through the electron transport chain of the mitochondria, O 2 •− generates H 2 O 2 , which is then split by catalase into water and oxygen or is partially reduced to hydroxide radical (•OH) in a Fenton reaction, causing a wider cellular oxidative damage (Feng et al, 2014) Bivalves are widely distributed in the water ecosystem. As these animals are lter feeders with poor locomotion ability, they are rather sensitive to the contamination of the aquatic environment by toxic metals, making them a group of important animals for aquatic toxicology research and for the evaluation of pollution by toxic metals (Chandurvelan et al, 2015;Chen et al, 2020;Ji et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are the key intracellular targets for Cd stress (Bhansali et al, 2017), and Cd exposure can damage the integrity of the mitochondria in aquatic organisms, both structurally and functionally (Adiele et al, 2011) Through the electron transport chain of the mitochondria, O 2 •− generates H 2 O 2 , which is then split by catalase into water and oxygen or is partially reduced to hydroxide radical (•OH) in a Fenton reaction, causing a wider cellular oxidative damage (Feng et al, 2014) Bivalves are widely distributed in the water ecosystem. As these animals are lter feeders with poor locomotion ability, they are rather sensitive to the contamination of the aquatic environment by toxic metals, making them a group of important animals for aquatic toxicology research and for the evaluation of pollution by toxic metals (Chandurvelan et al, 2015;Chen et al, 2020;Ji et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, defective mitophagy, which might be caused by long-term oxidative stress, is a common feature of several diseases, such as diabetes, atherosclerosis and neurodegenerative disease 4648 . Defective mitophagy occurs in the beta cells of obese T2DM patients, and PA treatment can lead to the dysfunction of mitophagy in beta cells in vitro 47 . In addition, defective mitophagy contributes to the production of mitochondrial ROS, the activation of NLRP3-dependent proinflammatory responses and the exacerbation of lipotoxicity 49 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that PA inhibited the transcription of PINK1, thus blocking the recognition of damaged mitochondria by autophagosomes. The PINK1/Parkin pathway is one of the important signaling pathways initiating the mitophagy of mitochondria with a low Δψm 47 . Full-length PINK1 (60 kDa) can be inserted into mitochondria but with different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted gene expression analyses of the MHO phenotype have been much more common. In one study, five out of six investigated mitophagy genes showed no significant differences in expression between MHO and metabolically healthy non-obese subjects[ 38 ]. The authors concluded that unaltered mitophagy allowed the control of oxidative stress and inflammation, leading to improved mitochondrial function and preserved insulin sensitivity in MHO subjects.…”
Section: Transcriptomicsmentioning
confidence: 99%